The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1159/000138024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extra- and Intracellular Calcium Blockers on Histamine and Antigen-Induced Bronchospasms in Guinea Pigs and Rats

Abstract: The extracellular calcium antagonists, nifedipine and verapamil, the mixed extra/intracellular calcium antagonist diazoxide and the intracellular calcium antagonist TMB-8 were studied for their effects on histamine-induced bronchospasm in guinea pigs and on antigen-induced bronchospasms in guinea pigs and rats when administered directly to the tracheobronchial tree. Nifedipine and verapamil inhibited histamine and antigen-induced bronchoconstriction in guinea pigs, and verapamil was effective in preventing ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…It is also shown that extracellular-site Ca 2+ -entry blockers inhibited histamine-and allergen-induced bronchoconstriction, whereas the intracellular-site Ca 2+ -entry blockers did not (24). It was proven that verapamil significantly worsened the bronchoconstriction induced by methacholine in vivo (23). Inhaled verapamil has been reported to produce bronchoconstriction (10,24,25).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also shown that extracellular-site Ca 2+ -entry blockers inhibited histamine-and allergen-induced bronchoconstriction, whereas the intracellular-site Ca 2+ -entry blockers did not (24). It was proven that verapamil significantly worsened the bronchoconstriction induced by methacholine in vivo (23). Inhaled verapamil has been reported to produce bronchoconstriction (10,24,25).…”
Section: Discussionmentioning
confidence: 97%
“…Inversely, other studies showed that VOC-blocking drugs, such as nifedipine, have proved disappointing as a therapy for asthma (19) and have a limited effect in alleviating bronchial constriction (20 -22). It was proven that blockade of L-type Ca 2+ channels at the extracellular (dihydropyridine and benzothiazepine group) rather than intracellular (phenylalkylamine group; e.g., verapamil) surface of the smooth muscle cell membrane may attenuate bronchoconstriction (23). It is also shown that extracellular-site Ca 2+ -entry blockers inhibited histamine-and allergen-induced bronchoconstriction, whereas the intracellular-site Ca 2+ -entry blockers did not (24).…”
Section: Discussionmentioning
confidence: 99%
“…So 1,4-DHPs classes of compounds are excellent starting synthons for the development of antitubercular agents [4][5][6]. As a result, newly synthesized generations of 1,4-DHPs possess different pharmacological activities such as anticancer [7], antidiabetic [8], antianginal [9], bronchodilating [10], neurotropic [11], antiallergic [12], anti-inflammatory [13], acaricidal, insecticidal, bactericidal, herbicidal [14] and other pharmacological activities [15]. These are used extensively in the treatment of angina pectoris, hypertension and arrhythmia [16] and some cardiovascular disorder.…”
Section: Introductionmentioning
confidence: 99%
“…1 The 1,4-DHPs cause vasorelaxation by blocking voltage-operated calcium channel in smooth muscle cells and also by increasing NO release from the intact endothelium. 2 Recently, some other pharmacological activities have been reported such as: antitumor, 3 bronchodilating, 4 antidiabetic, 5 antiviral 6 and antianginal. 7 The 1,4-DHPs have also been extensively utilised as analogs of NAD(P)H coenzymes to study the mechanism and synthetic potential of various redox processes.…”
Section: Introductionmentioning
confidence: 99%